2016
DOI: 10.1111/and.12710
|View full text |Cite
|
Sign up to set email alerts
|

46,XX males: a case series based on clinical and genetics evaluation

Abstract: 46,XX male sex reversal syndrome is one of the rarest sex chromosomal aberrations. The presence of SRY gene on one of the X chromosomes is the most frequent cause of this syndrome. Based on Y chromosome profile, there are SRY-positive and SRY-negative forms. The purpose of our study was to report first case series of Iranian patients and describe the different clinical appearances based on their genetic component. From the 8,114 azoospermic and severe oligozoospermic patients referred to Royan institute, we di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Most of the patients are diagnosed through genetic evaluation and related testing after puberty due to abnormal male phenotypes and infertility. The clinical manifestations of 46, XX male sex reversal syndrome vary with the presence or absence of SRY gene, involving some common features such as small testes, azoospermia, oligospermia, the differences in male phenotype, external genitalia, and female breast development 14,20,21 . In this case, clinical examinations revealed that the adult was a phenotypically normal male with bilateral smaller testes and azoospermia.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Most of the patients are diagnosed through genetic evaluation and related testing after puberty due to abnormal male phenotypes and infertility. The clinical manifestations of 46, XX male sex reversal syndrome vary with the presence or absence of SRY gene, involving some common features such as small testes, azoospermia, oligospermia, the differences in male phenotype, external genitalia, and female breast development 14,20,21 . In this case, clinical examinations revealed that the adult was a phenotypically normal male with bilateral smaller testes and azoospermia.…”
Section: Discussionmentioning
confidence: 79%
“…The presence of SRY causes the bipotential gonad to develop into testis, which plays a key role in determining human sex. The presence of the SRY gene determines the young man's normal male appearance with bilateral smaller testes caused by the lower level of testosterone hormones, which lead to the negative feedback effect—the higher levels of LH and FSH 2,14,22 . The patients with gonadal dysplasia are deficient in permatogenesis; however, they still have certain compensatory endocrine alterations to maintain the male phenotype and sexual behavior in adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The five structural abnormalities observed were Robertsonian and reciprocal translocations, deletion of the (Y) chromosome, and an inversion. Another small group of abnormal karyotypes comprised four cases of sex reversal (0.76%) with the 46, XX karyotype instead of the 46, XY normal karyotype, which features were described in a published study developed at the Royan Institute ( Mohammadpour Lashkari et al ., 2017 ). The analysis of abnormal karyotypes in the infertile control group revealed that 13 (4.33%) individuals had Klinefelter syndrome, a number as high as the one observed in the case group.…”
Section: Resultsmentioning
confidence: 98%
“…46,XX testicular disorder of sexual development (DSD), also known as de la Chapelle syndrome, is a rare condition (1 in 20,000-30,000 male individuals) in which a discrepancy exists between the phenotype and genotype of an individual ( Gilany et al ., 2015 ; Krausz & Riera-Escamilla, 2018 ; De La Chapelle et al, 1964 ; Mohammadpour Lashkari et al ., 2016 ). The main characteristics of individuals with 46,XX testicular DSD are having male external genitalia and azoospermia.…”
Section: Introductionmentioning
confidence: 99%